Orthotopic liver transplantation in familial amyloidotic polyneuropathy is associated with long-term progression of renal disease - Ferreira,Ana Carina (2012)
Orthotopic liver transplantation has become the treatment of choice for familial amyloidotic polyneuropathy. The aims of this study were to evaluate the renal complications post orthotopic liver transplantation in familial amyloidotic polyneuropathy and their impact. We retrospectively studied 185 recipients who underwent 217 orthotopic liver transplants. Mean age 3 6.8±9.5 years, 59% males, 14.3% with renal dysfunction pre orthotopic liver transplantation. Mean follow-up 3.6±3.7 years. Thirty-two patients died. Univariate and multivariate analysis were performed, and p<0.05 was considered significant. Acute kidney injury occurred in 57 patients and renal replacement therapy was needed in 16/57. In multivariate analysis, acute kidney injury was correlated with development of chronic kidney disease (p<0.001). Relating to development of chronic kidney disease, 23.5% had progress to stage 3, 6% to stage 4 and 5.1% to stage 5 d. According to Spearmen correlation, risk factors for chronic kidney disease development were age (p<0.001), renal dysfunction pre orthotopic liver transplantation (p<0.001) and acute kidney injury post orthotopic liver transplantation (p<0.001). Mortality was correlated with age (p<0.001), retransplantation need (p=0.004), renal dysfunction pre orthotopic liver transplantation (p<0.001), acute kidney injury post orthotopic liver transplantation (p=0.04), and chronic kidney disease stage 5 (p<0.001). Using binary regression, mortality was correlated with chronic kidney disease development (p=0.02). In conclusion, familial amyloidotic polyneuropathy patients are disposed to renal complications that have a negative impact on the survival of these patients